2007
DOI: 10.1080/00016340701253405
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound screening for fetal major abnormalities at 11–14 weeks

Abstract: The first-trimester scan is important in routine antenatal care for early detection of fetal defects, and determination of the fetuses at risk of cardiac anomalies and genetic syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…In experienced hands and with high-resolution ultrasound equipment the majority of severe malformations, as well as major CHD, may be detected by the end of the first trimester (Becker and Wegner, 2006;Dane et al, 2007;Lombardi et al, 2007;Chen et al, 2008;Timmerman et al, 2008;Timor-Trisch et al, 2009). This enables early reassurance for most women.…”
Section: Management Of Euploid Fetuses With Increased Ntmentioning
confidence: 99%
“…In experienced hands and with high-resolution ultrasound equipment the majority of severe malformations, as well as major CHD, may be detected by the end of the first trimester (Becker and Wegner, 2006;Dane et al, 2007;Lombardi et al, 2007;Chen et al, 2008;Timmerman et al, 2008;Timor-Trisch et al, 2009). This enables early reassurance for most women.…”
Section: Management Of Euploid Fetuses With Increased Ntmentioning
confidence: 99%
“…39 Using a complete morphology protocol is a prerequisite for high detection rates of major anomalies, which can reach around 80%. [10][11][12][13][14][15][16][17] This figure is not far from the efficiency of ST anomaly scan. 28,33,37,40 A systematic review on the ST anomaly scan effectiveness reported that about 45% of the major anomalies were detected routinely, 41 with large differences between studies in detection rates which ranged from 15 to 85%, and also large differences in overall detection rates according to the type of fetal anomaly.…”
Section: Introduction the First Trimester Anomaly Scanmentioning
confidence: 99%
“…In a series of 18 published screening studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17]34,[74][75][76] reporting on the effectiveness of the first-trimester scan in the diagnosis of fetal major abnormalities, all using a standard screening protocol, we numbered 118110 cases and we collected 5 cases diagnosed, and 34 cases missed. This underlines the difficulties encountered in OSB diagnosis in the FT. On the contrary, it is likely that adding at least a marker for OSB, we will be ending up by diagnosing the majority of cases, since introducing just a simple and reproducible parameter as BPD resulted in detecting half of the cases.…”
Section: Normal Aspects Osb Findingsmentioning
confidence: 99%
See 2 more Smart Citations